The vibrant family : a handbook for parents and professionals - Seidenfaden, Kirsten, ....-; Draiby, Piet, ....-; Soeborg Christensen, ....-; Davidsen, Mette-Marie, ....-; Draper, Rosalind, ....-; Bulman-May, James, ....- (London : Karnak, 2011)
Family life! We tackle it head-on with great enthusiasm and lots of hopes and dreams that our family will be filled with love, closeness, well-being and development. However, for many of us family life, parenthood, and our children develop in ways that we never anticipated and were looking forward to. Instead of creating a secure, confident, and vibrant family, all too many of us get helplessly caught up in daily quarrels. The result is that the children do not thrive and we have no clue what to do and how to move on. The Vibrant Family offers completely new and surprising approaches to parenthood. This book is not about child rearing, setting limits, or a specific way of communicating with children. It is about the ways in which well-being in our relationship is crucial to a good family life with confident and balanced children. The clear message of the book is that it is not the children who should change in order to get the family to function it is the parents. The book also offers practical and concrete tools to help you understand how you and your partner can learn to communicate and act in an accepting and close way, creating a climate in the family that encourages joy and growth.
We are all familiar with situations, events or stages in our lives, where we do not quite feel that we have succeeded as parents or partners. Parenthood is a unique opportunity not just to create a family, but also to create growth and development in our own lives, as well as in the lives of our children and with others with whom we are intimate. The Vibrant Family is a manual based on the new paradigms that have inspired the authors in their professional and personal lives. They have an optimistic approach and would like to invite you and your partner to develop some of the aspects of ourselves which we believe are crucial to your child's development. Reading this book you will also be in the process of developing your own relationship in quite a unique way. One of the messages of this book is that we as parents must take responsibility for all the emotions in the family environment - including those that exist between us as a couple. All too often we forget that our children live and are shaped in the atmosphere we, the adults, create in the family! The authors describe ways in which we can act in more confident, meaningful ways that enhance development with the people who are closest to us.
- The Vibrant Family - When Lovers Become Parents - Attachment and Exploration in Focus - The Brain - Our Invisible Greenhouse - The Transformative Power of Storytelling - Acknowledging Intimacy in Our Daily Lives - The Acknowledging Dialogue - The Acknowledging Dialogue for Parents - The Acknowledging Dialogue with Children - Acknowledging Relationships with Grandparents
Translated from Danish.
Includes bibliographical references and index.
Det levende familie.
Keywords: Familie; Families; Gezin; Ouderschap